Hubungan Kadar Bilirubin Indirek dengan Kadar Hemoglobin pada Bayi Ikterus Neonatus di Rumah Sakit X Yogyakarta - Qonita Amelia Fawwaz; Chairil Anwar; Titin Aryani (Yayasan Pendidikan Penelitian Pengabdian Algero, 2026)
Neonatal jaundice were frequently encountered condition in newborn infants, with an incidence rate of approximately 25% to 50% since first week in they life. Jaundice occurs due to excessive production of bilirubin in an infant’s body. This escalate in bilirubin grades is caused by the infant’s immature liver function, which is not yet able to process bilirubin optimally in the bloodstream. Theoretically, elevated bilirubin levels are associated with the breakdown of hemoglobin . This reseach was purposelly to established the relatiobship among indirect bilirubin grades also hemoglobin grades in infants with neonatal jaundice at Hospital X in Yogyakarta. This reseach was using a quantitative research design with a cross-sectional approach also employed secondary data included from medical records. A total of 31 samples of infants with neonatal jaundice from the 2024–2025 period shown the inclusion and exclusion criteria were analyzing to established the realtionship among the two variables. The correlation test results showed a coefficient of r = 0.249 with a significance level of p = 0.177 > 0.05, indicating a weak and statistically insignificant relationship between indirect bilirubin levels and hemoglobin levels. Based on these yields, it can be inferred don’t have statistically significant association exists among the two variables among infants with neonatal jaundice.